2004
DOI: 10.1190/1.1778232
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐dependent seismic response of fractured rock

Abstract: Effects of external stress and pore pressure variations on the seismic signature of fractured rocks remain of interest to geoscientists and practicing geophysicists. Commonly, the effects are modeled theoretically, assuming fracture faces to be rough surfaces contacting each other via the surface asperities. The model proposed here differs from other models of this kind in that (1) fracture roughness is described by a single parameter and (2) a controlled degree of hydraulic connectivity between fractures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…We will maintain the distance of the fractured reser voir constant, but the number of the cracks will be varied. Figures 7-9 show the fields of speeds for various densities of crack location in the reservoir (N = 3,4,5,7,9,13,21). Figure 10 shows the anisotropy of the response depending on the number of cracks.…”
Section: Dependence Of the Response On The Density Of The Location Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…We will maintain the distance of the fractured reser voir constant, but the number of the cracks will be varied. Figures 7-9 show the fields of speeds for various densities of crack location in the reservoir (N = 3,4,5,7,9,13,21). Figure 10 shows the anisotropy of the response depending on the number of cracks.…”
Section: Dependence Of the Response On The Density Of The Location Ofmentioning
confidence: 99%
“…For the mathematical modeling of seismic responses from frac tured hydrocarbon containing geological rocks, averaged models or models with effective coefficients of the medium are conventionally used in seismology [2][3][4][5][6][7]. This makes it necessary to introduce some empirical coefficients (e.g., coefficients of rock yielding [3][4][5][6]), additional hypotheses (e.g., the hypoth esis of linear sliding [3]). In our work, we investigate the possibility of complete numerical modeling of wave fields in the rocks with cracks based on the system of deformed solid mechanics equations, without introducing any empirical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they proposed the relation between stress and stiffness is nonlinear, and they showed that their theory is in good consistency with laboratory experiments (Yoshioka and Scholz, 1989b). Kozlov (2004) derives the normal and tangential compliances for dry fractures based on spherical contact Hertzian theory and by assuming regularly distributed asperity contacts separated by equal distance. Sevostianov and Kachanov (2008) apply and extend the results of Mindlin (1949) on normal and tangential compliances, which are described by the shape factor of the asperity contacts beside some the Young's modulus, shear modulus, and Poisson's ratio of the contact asperities.…”
Section: Introductionmentioning
confidence: 95%
“…King et al (1997) measured pressuredependence of the acoustic wave propagation in fractured rocks with aligned fractures and report the correlations between permeability and seismic velocities under a varying stress environment. Kozlov (2004), Duffaut and Landrø (2007), and Herwanger and Horne (2009) studied anisotropic seismic velocity changes caused by stress variations and their influences on reservoir monitoring and time-lapse AVO analysis. Among many other works, these studies demonstrate the importance of an accurate model that can effectively reproduce the velocity-stress relation for fractured rocks.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical simulation of seismic responses of fractured rock with hydrocarbon reservoirs is tra ditionally based on averaged models or models with effective medium coefficients [2][3][4][5][6][7], which imply the introduction of certain empirical coefficients (e.g., rock compliance coefficients [3][4][5][6]) and additional hypotheses (e.g., of linear slip [3]). In this paper, we explore the possibility of full numerical simulation of wave fields in fractured rock based on solid mechanics equations without introducing any empirical parameters.…”
Section: Introductionmentioning
confidence: 99%